A manufacturing scheduling approach by combining simulation technique with the Hodgson’s algorithm - Pinto, Telmo (2014)
The main objective of this paper consists on presenting an application of The Hodgson’s manufacturing scheduling algorithm applied ona production system model, through simulation technique. The simulation, executed on Arena, is applied to a model of a production environment for producing three new products, by using five different components. The components are processed on several work centres, which include different machines, organized on a job shop environment. The Hodgson’s algorithm is applied on a particular machine of the job shop, which consists on a bottleneck, and the main objective consists on minimizing the total number of tardy jobs on that bottleneck machine.